2007
DOI: 10.1002/ange.200703271
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Platinum Complexes and a Methionine Motif Found in Copper Transport Proteins

Abstract: Fremde Hilfe: Der Cu‐Transporter Ctr1, der in der Plasmamembran lokalisiert ist und methioninreiche Strukturmotive enthält, ist auch an der zellulären Aufnahme von Pt‐Tumortherapeutika beteiligt. Das methioninreiche Peptid Mets7 reagiert bereitwillig mit PtII‐Spezies, wobei sich cis‐ und trans‐[PtCl2(NH3)2] darin unterscheiden, dass letzteres bei der Reaktion mit Mets7 seine N‐Donorliganden behält. Die Pt‐Wirkstoffe gelangen möglicherweise durch vesikulären Transport in intakter Form zu den intrazellulären Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Alternatively, Cu(I) thiolation may induce conformational changes that bring the essential amino acid residues into close proximity, creating an intermolecular surface that allows Cu(I) to permeate into the cytoplasmic compartment. Previous in vitro assays demonstrated that bindings of Cu(I) (Hassett and Kosman, 1995) and CDDP (Arnesano et al, 2007) to methionine-rich motifs require completely naked forms of the metal ions. The interaction of CDDP with methionine, like Cu(I), was mostly by means of S-thiolation (Borch and Pleasants, 1979;Guo et al, 2004;Arnesano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, Cu(I) thiolation may induce conformational changes that bring the essential amino acid residues into close proximity, creating an intermolecular surface that allows Cu(I) to permeate into the cytoplasmic compartment. Previous in vitro assays demonstrated that bindings of Cu(I) (Hassett and Kosman, 1995) and CDDP (Arnesano et al, 2007) to methionine-rich motifs require completely naked forms of the metal ions. The interaction of CDDP with methionine, like Cu(I), was mostly by means of S-thiolation (Borch and Pleasants, 1979;Guo et al, 2004;Arnesano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro assays demonstrated that bindings of Cu(I) (Hassett and Kosman, 1995) and CDDP (Arnesano et al, 2007) to methionine-rich motifs require completely naked forms of the metal ions. The interaction of CDDP with methionine, like Cu(I), was mostly by means of S-thiolation (Borch and Pleasants, 1979;Guo et al, 2004;Arnesano et al, 2007). We demonstrated that both methionine mutations and membrane localization of hCtr1 are required for the dominant negative function for Cu(I) and CDDP transport.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the highly conserved region of the translated Atox1 gene in humans can be evidence for a vital role of Atox1 protein in human metabolism or embryonic development. This also might explain the still unknown phenotype of Atox1-mutation associated diseases [2] , even though different roles and regulatory factors for Atox1 in human metabolism are emerging out of recent studies [28][29][30][31] . One might speculate about a Menkes disease like phenotype resulting from a complete disruption of both functional alleles of Atox1 as suggested by Atox1 knockout mice data [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The list of cisplatin targets is constantly increasing and includes, for instance, transferrin [4], serum albumin [5][6][7], haemoglobin [3] or apo lipoproteins [7], ubiquitin [8] or metathioneins [9] or copper transport proteins [10]. Today, cisplatin-protein interactions are widely characterized by spectroscopic techniques (i.e.…”
Section: Introductionmentioning
confidence: 99%